Toward high‐performance lithium‐oxygen batteries with cobalt‐based transition metal oxide catalysts: Advanced strategies and mechanical insights. Issue 4 (18th December 2021) - Liu, Zhenjie; Zhao, Zhiwei; Zhang, Wang; Huang, Yang; Liu, Ying; Wu, Dianlun; Wang, Lei; Chou, Shulei
Abstract: Aprotic lithium‐oxygen (Li‐O2 ) batteries represent a promising next‐generation energy storage system due to their extremely high theoretical specific capacity compared with all known batteries. Their practical realization is impeded, however, by the sluggish kinetics for the most part, resulting in high overpotential and poor cycling performance. Due to the high catalytic activity and favorable stability of Co‐based transition metal oxides, they are regarded as the most likely candidate catalysts, facilitating researchers to solve the sluggish kinetics issue. Herein, this review first presents recent advanced design strategies for Co‐based transition metal oxides in Li‐O2 batteries. Then, the fundamental insights related to the catalytic processes of Co‐based transition metal oxides in traditional and novel Li‐O2 electrochemistry systems are summarized. Finally, we conclude with the current limitations and future development directions of Co‐based transition metal oxides, which will contribute to the rational design of catalysts and the practical applications of Li‐O2 batteries. Abstract : Advanced design strategies, fundamental insights, and challenges for Co x O y ‐catalyzed lithium‐oxygen batteries are critically analyzed, with possible development directions emphasized.